2018
DOI: 10.7196/ajhpe.2018.v10i1.959
|View full text |Cite
|
Sign up to set email alerts
|

The effect of undergraduate students on district health services delivery in the Western Cape Province, South Africa

Abstract: Background. The quality of care, attitudes of staff and long-term recruitment of practitioners have been shown internationally to improve health services as a result of a health facility accepting students for teaching. This study aimed to develop further insight regarding the impact of undergraduate student involvement on district health services in South Africa to understand the issues in a resource-constrained environment. Objectives. To describe the effect of the placement of undergraduate students on serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Even though the main objective of clinical education and training, which involves placing students on varied clinical platforms, is to develop specific clinical competencies in students, the positive impact of having students on a specific clinical platform is reported on by Reid et al [11] This is an important aspect to consider in settings where human resources for health are limited.…”
Section: Editorialmentioning
confidence: 99%
“…Even though the main objective of clinical education and training, which involves placing students on varied clinical platforms, is to develop specific clinical competencies in students, the positive impact of having students on a specific clinical platform is reported on by Reid et al [11] This is an important aspect to consider in settings where human resources for health are limited.…”
Section: Editorialmentioning
confidence: 99%
“…The TRPM placements were all undertaken in rural communities, defined as areas outside of major cities under the Modified Monash Model which characterises Australian geographic areas based on population and relative access to services [ 31 ]. Rural health student placements make an important contribution to WIL programmes internationally by boosting WIL numbers, servicing rural communities, contributing to students’ understanding of the complex relationship between socio-geographic location and health, and developing the future health workforce in these communities [ 32 , 33 , 34 ]. The TRPM placements focus on students working with specific population groups in a way that supports interprofessional learning opportunities and fosters respect for health consumers.…”
Section: Introductionmentioning
confidence: 99%
“…A publication by members of the Collaboration for Health Equity through Education and Research (CHEER) concluded that undergraduate students can add benefit to health services if health professions educators plan their clinical rotations, with the proviso of recognising the pressures under which their clinical supervisors work to deliver services to patients. 6 Significantly, the presiding policy perspective includes a call to transform the training of graduates and to align curricula with the international focus on social accountability and universal health coverage. This may be achieved through various methods, such as enrolling medical officers for a postgraduate primary care diploma 7 , training family physicians to scale 8 , as well as embracing the Academy of Science of South Africa (ASSAf) recommendations for socially accountable education.…”
mentioning
confidence: 99%